Aplicação de ultrassom em emulsões cárneas - Silva, Marianna Stefanello (2017)
Meat emulsions are complex systems that generate meat products like mortadellas, sausages, among others. Ultrasound (US) application enables improvements in traditional food processes. In this study, different operational modes (normal, degas and sweep) of US at 25 kHz, with 60% amplitude for 6 minutes, in pork (subsequent emulsion elaboration) and in ready emulsion (experiment 1) were evaluated. After finding the best operating mode, different times (0,6,9 and 12 minutes) were used for the application of pork and ready-to-use emulsion (experiment 2), where they were analyzed for pH, oxy-reduction potential (mV), yield, stability, texture profile, oxidative processes and temperature monitoring of US application in both experiments. In the experiment 1 the normal mode of operation, applying US in the meat, did not have a positive effect on the yield, already in emulsions treated with US at the end, promoted greater yield and stability, besides modifying the texture parameters compared to the control. The improvements provided by the US regarding technological quality were observed in the normal mode and in this way, the second stage was designed. With 9 minutes of sonication in the meat, the US favored yield and stability. In finished emulsions, the US (time of 12 minutes) was shown to help improve the technological parameters. For the experiment with the application of US (25 kHz, 60% amplitude) with different modes (degas, normal and sweep) in the entire process of manufacturing meaty emulsions, plus sonication of 6 minutes in the finished emulsion, the characteristics physical properties (moisture, ash, proteins, lipids, pH and mV), technological properties (yield and stability), instrumental texture (hardness, cohesiveness and chewability), lipid oxidations (thiobarbituric acid reactive substances). The performance, the normal mode stood out. For the evaluation of the instrumental texture, the sweep mode obtained better results. The TBARS values did not increase in the different US modes. Low carbonyl values were found in the normal mode, however, those of the thiol in this mode decreased indicating oxidation. The US did not promote a temperature increase capable of destabilizing the emulsions in both experiments, thus allowing its use. The use of the US in the preparation of meat emulsions has demonstrated that this technology can be employed which provides reduced preparation time and increased yield.